Tridimensional Retinoblastoma Cultures as Vitreous Seeds Models for Live-Cell Imaging of Chemotherapy Penetration - Winter, Ursula Andrea (2019)
A preclinical model could aid in understanding retinoblastoma vitreous seeds behavior, drug penetration, and response to chemotherapy to optimize patient treatment. Our aim was to develop a tridimensional in vitro model of retinoblastoma vitreous seeds to assess chemotherapy penetration by means of live-cell imaging. Cell cultures from patients with retinoblastoma who underwent upfront enucleation were established and thoroughly characterized for authentication of human tumor origin. The correlation of the in vitro tridimensional structures resembling human spheres and dusts vitreous seeds was established. Confocal microscopy was used to quantify real-time fluorescence of topotecan as a measure of its penetration into different sizes of spheres. Cell viability was determined after chemotherapy penetration. The in vitro spheres and dusts models were able to recapitulate the morphology, phenotype, and genotype of patient vitreous seeds. The larger the size of the spheres, the longer the time required for the drug to fully penetrate into the core (p < 0.05). Importantly, topotecan penetration correlated with its cytotoxic activity. Therefore, the studied tridimensional cell model recapitulated several characteristics of vitreous seeds observed in patients with retinoblastoma and were successfully used to assess live-cell imaging of chemotherapy penetration for drug distribution studies.